From Sasanian Adurbadagan to Modern Azerbaijan: Historical Background and Developments - Khalifa-Zadeh , Mahir; Khalifazadeh , Leyla (Recent Trends in Arts and Social Studies Vol. 9, 2023)
The author discusses the historical background of the origin of modern Azerbaijan divided by the Araz river into southern or Iranian and northern or the independent Republic of Azerbaijan. The author analyzes the application of the Sasanian name Adurbadagan to both sides of modern Azerbaijan. He believes that the name Azerbaijan originates from the Avestan words Atash or Atar or Azar that means fire. As a historical and political term, Azerbaijan roots deep to Achaemenids’ Aturpatakan (Atropatena) evolving into the Sasanian Adurbadagan - a Zoroastrian center of the empire. Since late Antiquity, Adurbadagan’s military and administrative functions were extended and applied by the Sasanids to all lands in the north from the Aras river, up to Darband fortress in Arran (Albania) in Caucasia. The author argue, since late Antiquity, Adurbadagan and Arran became interchangeable names in the northern bank of the Araz river. In the Islamic period, particularly after Seljuk Turks conquest of Iran, Adurbadagan evolved into the Turkified form of Azarbadajan or Azerbaijan, cementing the modern Azerbaijani Turks’ identity in the south and north sides of the entire Azerbaijan divided by the Araxes.